North Sumatra's Food Availability Model: Technology Adoption, Farmer Organization Support, and Geographic Variability - Lubis, Mitra Musika (Quantitative Economics and Management Studies, 2025)
AbstractFood availability is a strategic issue affecting economic stability and community welfare, particularly in agrarian regions such as North Sumatra Province. This study aims to analyze factors influencing food availability, including institutional support, geographic variation, and the adoption of agricultural technology. Data were collected through a survey of 100 rice farmers in Percut District, Deli Serdang Regency, using a structured questionnaire. Analysis was conducted using Structural Equation Modeling (SEM) with Smart PLS software to evaluate validity, reliability, and relationships among variables. The results indicate that institutional support and geographic variation significantly affect food availability, while the adoption of modern agricultural technology does not show a significant effect. Institutional support, including training, extension services, and production facilitation, enhances farmers’ productivity, whereas physical environmental conditions, such as soil quality, topography, and rainfall, are primary determinants of production success. These findings emphasize the importance of strengthening institutional capacity and regional management as policy priorities, while technology implementation should be adapted to local needs and farmers’ capacities. Limitations include a restricted geographic scope and technology variables that do not fully capture modern agricultural complexity. This study provides a conceptual foundation for strategies aimed at enhancing food security and guiding local policy interventions. Keywords:. Agricultural productivity; Food availability; Geographic variation; Institutional support; Technology adoptionagricultural productivity